The negotiation of masculinity by young, male peer counselors - Davies, Nicholas Charles Christopher (My University, 2008)
This study was directed at exploring the personal constructions of young males who had self selected as peer counselors, of what it means to be a man in South Africa at this time in history. One of the goals identified was to highlight and examine both hegemonic and alternative versions of masculinity and, in particular, to examine how young men position themselves in relation to these constructions. In order to investigate the research question, ten adolescents/young men participated in focus group discussions on the topic of masculinity. The participants included 8 school boys, 5 white and 3 black, attending a private, all boys school, as well as 2 black university students. All participants had self selected as peer counselors. The study is located in the qualitative research tradition which allows for depth of description and interpretation. The three focus group discussions held (two at the boys school with 4 participants in each, and one at the university) were recorded and transcribed verbatim. These transcripts were then subject to a critical thematic content analysis. The main themes were identified and the four themes which emerged as dominant in the conversation and occurred most regularly across all three groups are analyzed and discussed. These themes are emotional stoicism, normative heterosexuality, gendered division of labour and displayed toughness. Under each theme material supporting hegemonic constructions of masculinity and material supporting alternative constructions of masculinity is discussed as a separate sub-theme. The impact of the role as peer counselor on participants constructions of masculinity is also discussed. A brief meta-theoretical discourse analytic commentary is also provided, addressing for example, strategies employed by participants to maintain their sense of masculinity in the discussions. This study highlights the fluidity and plurality of masculinity as well as the struggle of adolescent boys and young men as they engage with where and how to position themselves as masculine. A main finding or observation is that some degree of alternative masculinity will be countenanced provided there is evidence of an acceptable baseline of hegemonic or traditional masculinity in a boy or man.
Keywords: Masculinity; Gender identity